2015
DOI: 10.1186/s40529-015-0114-6
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis SFAR4 is a novel GDSL-type esterase involved in fatty acid degradation and glucose tolerance

Abstract: Background SFARs (seed fatty acid reducers) belonging to the GDSL lipases/esterases family have been reported to reduce fatty acid storage and composition in mature Arabidopsis seeds. GDSL lipases/esterases are hydrolytic enzymes that possess multifunctional properties, such as broad substrate specificity, regiospecificity, and stereoselectivity. Studies on the physiological functions and biochemical characteristics of GDSL lipases/esterases in plants are limited, so it is important to elucidate the molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 45 publications
1
56
0
1
Order By: Relevance
“…Major advances have been reported that GDSL lipases/esterases are involved in various biological functions, such as development of seeds [5][6][7][8][9], deposition of epicuticular wax [10], biosynthesis of cutin [11,12], hydration of pollen [13] and regulation of plant cell wall components [14]. Moreover, GDSL lipases are also involved in responses to various abiotic stresses, such as salt [15], drought [16], and freezing [17], as well as to biotic stresses, such as plant immune responses and pathogen defense [18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Major advances have been reported that GDSL lipases/esterases are involved in various biological functions, such as development of seeds [5][6][7][8][9], deposition of epicuticular wax [10], biosynthesis of cutin [11,12], hydration of pollen [13] and regulation of plant cell wall components [14]. Moreover, GDSL lipases are also involved in responses to various abiotic stresses, such as salt [15], drought [16], and freezing [17], as well as to biotic stresses, such as plant immune responses and pathogen defense [18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that the substratebinding pocket of GDSL-hydrolases is flexible, allowing a broader substrate specificity (Akoh et al, 2004). The genome of Arabidopsis contains > 100 putative GDSL lipases, and some of them have been studied in some detail (Kelly & Feussner, 2016) and show, for example, esterase activity against artificial substrates (Huang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…SFAR4 , a GDSL‐type esterase. SFAR4 plays an important role in fatty acid degradation (Huang et al ), and its primary metabolites function in plant disease resistance (Bolton ). Pectin is a major constituent of the primary cell wall, and pectin hydrolysis will cause cells to separate from each other (Fry , Harholt et al ).…”
Section: Discussionmentioning
confidence: 99%